Effects of hanger reflex on the cervical muscular activation and function: A surface electromyography assessment - Wang, Dian; Liu, Baoge (Frontiers in Physiology, 2022)
Introduction: Cervical muscular dysfunction is closely associated with disorders and neuromuscular diseases of the cervical spine, and the hanger reflex (HR) has the potential to become a rehabilitation method. The muscular electrophysiology mechanism of HR is unclear. This study aims to identify the impacts of HR on cervical rotators’ myoelectrical activity and function. Methods: We designed a self-control clinical trial, and asymptomatic volunteers were continuously included from 1 September 2021 to 30 April 2022 in our department. Rotation tasks were performed on both sides under each of the situations: no HR, unilateral HR, and bilateral HR. Surface electromyography (SEMG) was used to detect the myoelectrical activity of agonistic splenius capitis (SPL), upper trapezius (UTr), and sternocleidomastoid (SCM). The co-contraction ratio (CCR) during rotation tasks was calculated. Correlation analyses and multiple linear regression were performed. Results: Finally, 90 subjects were enrolled (power >90%). The adjusted EMG value (aEMG) of SPL UTr, SCM, and rotating CCR under the unilateral HR and bilateral HR were higher than no HR; the aEMG of SPL and rotating CCR under the bilateral HR were higher than the unilateral HR. Multiple linear regression showed that HR pattern and age were the independent affecting factors for the aEMG of SPL (p < 0.001, p < 0.001), UTr (p < 0.001, p < 0.001), and SCM (p < 0.001, p < 0.001); BMI was an independent affecting factor for the aEMG of SPL (p < 0.001) and SCM (p < 0.001); HR pattern was the only affecting factor for CCR (p < 0.001). Conclusion: HR can increase the cervical rotators’ myoelectrical activities and rotating CCR, and the effects of bilateral HR are greater than unilateral HR, suggesting that bilateral HR has a greater clinical potential to become a rehabilitation method for treating cervical neuromuscular disorders.